T-Cell Response to Viral Hemorrhagic Fevers - Perdomo-Celis, Federico; Salvato, Maria S.; Medina-Moreno, Sandra; Zapata, Juan C. (Vaccines (Basel), 2019)
Viral hemorrhagic fevers (VHF) are a group of clinically similar diseases that can be caused by enveloped RNA viruses primarily from the families Arenaviridae, Filoviridae, Hantaviridae, and Flaviviridae. Clinically, this group of diseases has in common fever, fatigue, dizziness, muscle aches, and other associated symptoms that can progress to vascular leakage, bleeding and multi-organ failure. Most of these viruses are zoonotic causing asymptomatic infections in the primary host, but in human beings, the infection can be lethal. Clinical and experimental evidence suggest that the T-cell response is needed for protection against VHF, but can also cause damage to the host, and play an important role in disease pathogenesis. Here, we present a review of the T-cell immune responses to VHF and insights into the possible ways to improve counter-measures for these viral agents.